Evaluation of long-term oncological outcomes of colon cancer resections in octogenarian and nonagenarian patients (Annals of Medical Research, 2021)
Aim: To investigate the long-term oncologic results of patients older than 80 years who were operated on for colon cancer in our clinic. Material and Methods: All patients who were operated on for colon cancer in our clinic between 2006 and 2013 were included. Data were collected retrospectively by chart review. The final status of the patients was obtained by questionnaires answered by patients or patients’ relatives. Patients were divided into two groups according to their age, over 80 years of age and under 80 years of age, respectively. The following data were compared between groups; gender, pathological data, oncological treatment, one-year survival, disease-free survival and 5-year overall survival.Results: A total of 188 patients were included. There were 13 (6.9%) patients over 80 years of age. The expected 5-year survival rate under the age of 80 was 77.4%, while it was 46.2% for over the age of 80 (p = 0.001). The 5-year disease-free survival was calculated as 77% for under 80 years and 38.5% for over 80 years (p = 0.001). In the postoperative first year, 8 (4.6%) patients under 80 years of age and 1 (7.7%) of patients over 80 years of age died. Nine of 13 (69.2%) patients over 80 years of age died during follow-up.Conclusion: : In the light of the findings of our study, it can be said that the first 1-year survival rate of patients older than 80 years was similar to the younger patients, but they had worse survival rates in the longer term.
Keywords: Colon cancer; octogenarians; long term survival; colon surgery